2010
DOI: 10.1002/ejoc.201001219
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Allylation of Aldehydes Catalyzed by Diastereoisomeric Bis(tetrahydroisoquinoline) N,N′‐Dioxides

Abstract: Enantioselective allylation of aromatic and α,β‐unsaturated aldehydes with allyltrichlorosilane catalyzed by two diastereoisomeric (R,Rax,R)‐ and (R,Sax,R)‐bis‐1,1′‐[5,6,7,8‐tetrahydro‐3‐(tetrahydrofuran‐2‐yl)isoquinoline] N,N′‐dioxideswas studied. The course of the reaction was profoundly influenced by the chosen solvent. The (R,Sax,R) catalyst efficiently promoted the reaction in THF with enantioselectivity up to 96 %. On the other hand, the allylation of aromatic aldehydes in the presence of the (R,Rax,R) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Interestingly, allylation experiments have shown that the N , N′ ‐dioxide catalysts 4 and 5 , developed in this laboratory [it should be appreciated that their design was inspired by the elegant synthesis and use of QUINOX (a mono N ‐oxide containing an element of axial chirality) by Kočovský and Malkov] give the best results in terms of asymmetric induction and yields in THF and other nonpolar solvents. The R ‐catalysts in this instance give rise to homoallylic R ‐alcohols, and the S ‐catalysts give rise to homoallylic S ‐alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, allylation experiments have shown that the N , N′ ‐dioxide catalysts 4 and 5 , developed in this laboratory [it should be appreciated that their design was inspired by the elegant synthesis and use of QUINOX (a mono N ‐oxide containing an element of axial chirality) by Kočovský and Malkov] give the best results in terms of asymmetric induction and yields in THF and other nonpolar solvents. The R ‐catalysts in this instance give rise to homoallylic R ‐alcohols, and the S ‐catalysts give rise to homoallylic S ‐alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ( R,S ) ‐1 provided the ( S )‐ 4 with excellent enantioselectivity in THF of 97% and 96% ee at −78 °C and −40 °C, respectively (entries 5 and 6). Not surprisingly,18a,c,d,h the reactions carried out in dichloromethane furnished the homoallyl alcohols with opposite configurations: ( R,R )‐ 1 gave ( S )‐ 4 and ( R,S ) ‐1 gave ( R )‐ 4 with significantly lower asymmetric inductions in the range of 18–53% ee (entries 3, 4, 7, and 8).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the appropriate choice of solvent is crucial for asymmetric induction, rate, and yield of the allylation reaction 21. Therefore, catalyst 8 was tested in the most common solvents used for this type of asymmetric reaction (Table 2).…”
Section: Resultsmentioning
confidence: 99%